IMPLEMENTASI PERATURAN DAERAH KABUPATEN PEMALANG NOMOR 6 TAHUN 2008 TENTANG KAWASAN PARIWISATA PANTAI WIDURI DALAM PERSPEKTIF EDWARDS - Syariffudin, Arif; Suhardiyanto, Andi; Seftyono, Cahyo (Program Studi Ilmu Politik Fakultas Ilmu Sosial Universitas Negeri Semarang, 2018)
The development of beach tourism could increase original local income, in that case Pemalang Regency?s government made a Local Rregulation to optimize the potential of Widuri Beach tourism. The objective of this research is: (1) What are Pemalang Regency?s government policy corresponding to the Pemalang  Regency?s Local Regulation Number 6 Year 2008 relating about Widuri Beach Tourism Area. (2) How is the implementation of Pemalang Regency?s Local Regulation number 6 year 2008 relating about Widuri Beach Tourism Area. The research methods that was used in this research is qualitative research. The type of data that was used is primary and secondary data. The data collecting technique was using observation technique, interviews and documentation. This research was using qualitative analysis which covers data reduction technique, data presentation and data conclusion. The result of this research shows that: (1) Pemalang Regency?s Government policy corresponding to Pemalang Regency?s Local Regulation number 6 year 2008 relating about Widuri Beach Tourism Area which are: (a) The policy of development of tourism facilities and infrastructure (b) Guidance, arrangement, supervision and control of tourism (2) The implementation of Pemalang Regency?s Local Regulation number 6 year 2008 relating about Widuri Beach Tourism Area based on Edwards? perspective, which are: (a) Communication are done through direct meeting, coordination meeting and socialization (b) Resources, resources in the implementation of this local regulation, whether in the human resources or money resources, both are very limited. The money resources came from APBN and APBD. The limited human resources can be supported with the help of contract employee (c) Dispositions, the implementers do the task based on the directives of the local regulation and the leader (d) Bureaucratic structure, bureaucratic structure is not effective and efficient and cause the employee to be burdened, but the government can maximize that bureaucratic structure. The researcher suggests that: It is necessary to increase the budget from Pemalang Regency?s Government to support the regional development of Widuri Beach Tourism Area optimally and it is necessary to increase the human resources based on the fiels that needed.